The influence of conservative management of premature rupture of the membrane On infant Morbidity and mortality - Risanto Siswosudarmo, Risanto Siswosudarmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1991)
Premature rupture of the membrane (PROM) still gives a great problem in obstetrics because of its high perinatal morbidity and mortality, and whether conservative or active management should be taken is still debatable. The aim of the present study is to evaluate a conservative management of PROM especially on infant morbidity and mortality. A total of 130 PROM cases with gestational age of 28 weeks or more and birth weight of 1000 grams or more were included into the study. Twin and major congenital anomalies were excluded. A total of 129 non-PROM cases during the same period were selected randomly serving as control. Data were processed with IBM compatible personal computer using version 2.0 SPSS program: t-test, chi-square test and relative risk (RR) were statistical analysis used in this study.Both groups were comparable, in terms of gestational age, birth weight, type of presentation, but not in parity. Results showed that the risk of getting neonatal infection was 1.82 (0.95-3.46). Although it was not statistically different, but i t was clinically important. Rupture of membrane more than 48 hours gave the highest risk of neonatal infection (RR 2.77; 95% CL 0.95-8.05). Neonatal asphyxia was more common in the PROM group compared to the non-PROM. One minute Apgar score indicated that the risk of severe asphyxia was 2.19 (L44-3.33) and the risk ofmoderate asphyxia was 1.84 (1.19-2.87). Evaluation after five minutes showed that such risk became 1.56 (0.12-19.19) and 3.13 (1.65-5.93) respectively. Perinatal death in both groups did not show significant difference, but neonatal death due to sepsis in the PROM group was about four-folds compared to the non-PROM. Death atrributed to respiratory distress syndrome did not show significant difference.The study concluded that conservative management resulted in a high infant morbidity, although the infant mortality was relatively the same. As neonatal asphyxia was more common in the PROM group, then adequate resuscitation should be prepared. Although prophylactic antibiotics had been given, neonatal death due to infection was still high.Key Words: PROM - neonatal infection - asphyxia - obstetrics - infant mortality